A phase II study of belumosudil for chronic graft-versus-host disease in patients who failed at least one line of systemic therapy in China - Wang, Ying; Wu, Depei; Zhang, Xiang; Li, Yuhua; He, Yanjie; Liu, Qifa; Xuan, Li; Li, Zhenyu; Qi, Kunming; Sun, Yuqian; Wang, Shunqing; Mo, Wenjian; et al. (BMC medicine, 2024)
Chronic graft-versus-host disease (cGVHD) is an immune-related disorder that is the most common complication post-allogenic hematopoietic stem cell transplant. Corticosteroids with or without calcineurin inhibitors (CNIs) remain the mainstay of cGVHD treatment for first-line therapy. However, for many patients, cGVHD symptoms cannot be effectively managed and thus require second-line therapy. Currently, there is no approved treatment for second-line cGVHD treatment in China. In this study, belumosudil, a highly selective and potent rho-associated coiled-coil-containing protein kinase-2 inhibitor demonstrated to be effective for cGVHD in the United States and other Western countries, is investigated in patients with cGVHD in China for its overall benefit-risk balance. This multicenter, open-label phase II study evaluated the safety, efficacy, and pharmacokinetics of oral belumosudil 200 mg once daily in cGVHD patients who had been treated with at least one line of systemic therapy in China. The primary endpoint was overall response rate (ORR); each individual patient's response was assessed by the investigator using the 2014 National Institutes of Health consensus criteria. Secondary endpoints were duration of response (DOR), time to response (TTR), changes in Lee Symptom Scale (LSS) score, organ response rate, corticosteroid dose change, CNI dose change, failure-free survival, time-to-next-treatment, overall survival, and safety. Thirty patients were enrolled in the study with a median follow-up time of 12.9 months. ORR was 73.3% (95% confidence interval: 54.1-87.7%) and all responders achieved partial response. Median DOR among responders was not reached and median TTR was 4.3 weeks (range: 3.9-48.1). Fifteen patients (50.0%) achieved clinically meaningful response in terms of reduction in LSS score by ≥ 7 points from baseline. Corticosteroid and CNI dose reductions were reported in 56.7% (17/30) and 35.0% (7/20) of patients, respectively. Most treatment-emergent adverse events (TEAEs) were mild to moderate in severity, with 11 patients (36.7%) experiencing grade ≥ 3 TEAEs. The most common grade ≥ 3 TEAE was pneumonia (n = 5, 16.7%). Belumosudil treatment demonstrated a favorable benefit-risk balance in treating cGVHD patients who previously have had standard corticosteroid therapy in China where approved second-line setting is absent. ClinicalTrials.gov identifier NCT04930562.